2013
DOI: 10.1165/rcmb.2012-0146oc
|View full text |Cite
|
Sign up to set email alerts
|

Ciliated Cells of Pseudostratified Airway Epithelium Do Not Become Mucous Cells after Ovalbumin Challenge

Abstract: Mucous cell metaplasia is a hallmark of airway diseases, such as asthma and chronic obstructive pulmonary disease. The majority of human airway epithelium is pseudostratified, but the cell of origin of mucous cells has not been definitively established in this type of airway epithelium. There is evidence that ciliated, club cell (Clara), and basal cells can all give rise to mucus-producing cells in different contexts. Because pseudostratified airway epithelium contains distinct progenitor cells from simple col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…In the lungs of humans, as well as other mammals, this region of the airway also contains goblet cells, which are marked by expression of the transcription factor SPDEF and mucin-5ac (Muc5ac). Cell lineage–tracing studies in mice have shown that goblet cells, which arise in mice only after injury or in disease states, are derived from secretoglobin family 1a member 1–expressing (Scgb1a1 + ) secretory cells and not ciliated epithelial cells in the postnatal lung after injury 45 . Studies grafting basal and luminal cell populations into tracheas denuded of epithelium in mice followed by implantation of the reseeded tracheal xenografts into immunodeficient mice suggest that either basal or luminal cells can regenerate the tracheal epithe-lium 40,46,47 .…”
Section: Candidate Stem Cells Of the Respiratory Systemmentioning
confidence: 99%
“…In the lungs of humans, as well as other mammals, this region of the airway also contains goblet cells, which are marked by expression of the transcription factor SPDEF and mucin-5ac (Muc5ac). Cell lineage–tracing studies in mice have shown that goblet cells, which arise in mice only after injury or in disease states, are derived from secretoglobin family 1a member 1–expressing (Scgb1a1 + ) secretory cells and not ciliated epithelial cells in the postnatal lung after injury 45 . Studies grafting basal and luminal cell populations into tracheas denuded of epithelium in mice followed by implantation of the reseeded tracheal xenografts into immunodeficient mice suggest that either basal or luminal cells can regenerate the tracheal epithe-lium 40,46,47 .…”
Section: Candidate Stem Cells Of the Respiratory Systemmentioning
confidence: 99%
“…Immunofluorescent detection has been described previously (Kim et al, 2012; Pardo-Saganta et al, 2013; Tata et al, 2013a). Briefly, the detection of Notch2 intracellular domain and of c-myb required signal amplification.…”
Section: Immunofluorescence Microscopy and Imagingmentioning
confidence: 99%
“…Mouse tracheal basal cells were obtained and cultured as previously described (Pardo-Saganta et al 2013; Tata et al 2013a; Zhao et al 2014). Lentiviral vectors expressing murine N2ICD were generated from 3XFlagNICD2 plasmid (Addgene, 20184).…”
Section: Cell Culture and Viral Transductionmentioning
confidence: 99%
“…However, unlike human airways, mouse airways have few mucin‐producing cells under normal conditions. Allergen exposure induces mucus overproduction by up‐regulating mucin expression in secretory cells (2, 3). While the origin of cells that produce mucin differs between humans and mice, mechanisms underlying mucus overproduction in allergic inflammation are evolutionally conserved.…”
mentioning
confidence: 99%